2007
DOI: 10.1111/j.1551-2916.2007.01962.x
|View full text |Cite
|
Sign up to set email alerts
|

Compositional Inhomogeneity in Li‐ and Ta‐Modified (K, Na)NbO3 Ceramics

Abstract: Compositional inhomogeneity is examined in Li-and Ta-modified potassium sodium niobate (K,Na)NbO 3 perovskite ceramics. The inhomogeneous distribution of the A-site (K and Na) and B-site (Nb and Ta) cations is found to be correlative. The inhomogeneity could not be eliminated by prolonged hightemperature annealing in samples prepared by direct mixing of alkaline carbonates and Ta and Nb oxides. In contrast, the precursor method, where a (Nb x Ta 1Àx ) 2 O 5 solid solution was first formed, led to a considerabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
139
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(149 citation statements)
references
References 26 publications
10
139
0
Order By: Relevance
“…Several issues have been discussed in the literature: (i) high hygroscopicity of the starting alkaline carbonate powders, especially K 2 CO 3 , and high volatility of alkaline oxides at elevated temperatures, both creating difficulties in controlling the stoichiometry, 275,[278][279][280][281][282][283][284] (ii) formation of secondary phases, some of which are hygroscopic, 275,285 and (iii) difficulty in achieving high compositional homogeneity, especially at the B-site of the perovskite ABO 3 lattice, when KNN is modified with, for example, Ta, such as in the case of (K,Na,Li)(Nb,Ta)O 3 (KNLNT) solid solution. 286,287 KNN is usually prepared by the solid-state reaction, mostly from a mixture of alkaline carbonates and Nb 2 O 5 . 288 Despite the high technological importance of KNN, remarkable progress in the understanding of the solid-state synthesis of this material has only been made recently.…”
Section: Other Oxidic Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several issues have been discussed in the literature: (i) high hygroscopicity of the starting alkaline carbonate powders, especially K 2 CO 3 , and high volatility of alkaline oxides at elevated temperatures, both creating difficulties in controlling the stoichiometry, 275,[278][279][280][281][282][283][284] (ii) formation of secondary phases, some of which are hygroscopic, 275,285 and (iii) difficulty in achieving high compositional homogeneity, especially at the B-site of the perovskite ABO 3 lattice, when KNN is modified with, for example, Ta, such as in the case of (K,Na,Li)(Nb,Ta)O 3 (KNLNT) solid solution. 286,287 KNN is usually prepared by the solid-state reaction, mostly from a mixture of alkaline carbonates and Nb 2 O 5 . 288 Despite the high technological importance of KNN, remarkable progress in the understanding of the solid-state synthesis of this material has only been made recently.…”
Section: Other Oxidic Systemsmentioning
confidence: 99%
“…In fact, studies on KNLNT showed that such inhomogeneities, once formed, were not eliminated by prolonged high-temperature annealing and/or intensive attrition milling applied after each calcination step. 286 The key question is whether it is in principle possible to modify the diffusion-limited process to such an extent that it would result in another reaction pathway. In the following we show that this may be achieved by the mechanochemical approach.…”
Section: Other Oxidic Systemsmentioning
confidence: 99%
“…It has been found that a narrow sintering range exists (Y. Wang et al, 2007) where the materials experience considerable changes in the grain size, density, appearance of secondary phases, liquid phase, and then the piezoelectric and ferroelectric properties change as well. In the text below, are discussed some of the sintering methods used for the conformation of KNN ceramics.…”
Section: Sintering Of Knn and Related Compositionsmentioning
confidence: 99%
“…The method is simple and economic comparing with HP or SPS which will be described in the next sections. Most studies about KNN and related compositions use conventional sintering (Chang et al, 2007;Egerton & Dillon, 1959;Hao et al, 2009;Park et al, 2007;Saito & Takao, 2006;Y. Wang et al, 2007;Zuo et al, 2007), and just some papers report lead-free piezoceramics sintered by HP or SPS.…”
Section: Conventional Sinteringmentioning
confidence: 99%
See 1 more Smart Citation